GLIOMAS GENETIC MARKERS AND PREFERENTIAL SUPRATENTORIAL BRAIN LOCATIONS. (3rd October 2018) - Phang, Isaac; Craig-Mcquaide, Anna; Mavrakis, Adamantios; Grivas, Athanasios
Abstract: INTRODUCTION: Gliomas are associated with preferential locations in secondary functional areas. We examine our data to see if there is a genetic difference between the gliomas in different supratentorial locations using IDH-1, MGMT methylation and 1p19q co-deletion status. Methods WHO Grade II and III glioma patients with histology were included retrospectively from the MDT database from 2013 – 2017. Glioma location was determined by the MRI report. In cases where the glioma expanded beyond one lobe, consensus was obtained between the authors to determine where the majority of the tumour bulk was located. IDH-1, MGMT methylation and 1p19q co-deletion status were obtained from the histopathology report. χ 2 test with Bonferroni correction was used to compare the actual and expected numbers observed. Results191 gliomas were included. There were 55 astrocytomas Grade II, 81 astrocytomas Grade III, 24 oligodendrogliomas Grade II, 29 oligodendrogliomas Grade III and 2 anaplastic pleomorphic xanthoastrocytomas. There were 74 frontal, 25 insular, 64 temporal, 20 parietal and 8 basal ganglia tumours. 64.1% of the gliomas were IDH-1 mutated. However, 82.4% in the frontal lobe, 70.8% in the insula, 46.2% in the temporal lobe, 60.0% in the parietal lobe and 14.3% in the basal ganglia regions were IDH-1 mutated (p< 0.001). 57.3% of the gliomas were MGMT methylated. However, 64.9% in the frontal lobe, 62.5% in the insula, 50.8% in the temporal lobe, 60.0% in the parietal lobe and 42.9% in the basal ganglia regions were MGMT methylated (p<0.001). 31.3% of the gliomas were 1p19q co-deleted. However, 43.2% in the frontal lobe, 29.2% in the insula, 23.1% in the temporal lobe, 25% in the parietal lobe and none in the basal ganglia were 1p19q co-deleted (p<0.001). CONCLUSION: Our data suggest gliomas in different supratentorial locations have genetic differences based on the three genetic markers.